RAD54-Like Protein 2 Is a Potential Diagnostic and Prognostic Biomarker in Head and Neck Squamous Cell Carcinoma - Xu, Xingnong; Ma, Lei (ENT Updates, 2025)
Head and Neck Squamous Cell Carcinoma (HNSCC) poses a major global health challenge, highlighting the demand for reliable biomarkers to enable earlier detection and improve patient survival. This study sought to evaluate the diagnostic and prognostic significance of RAD54-like Protein 2 (RAD54L2) in HNSCC. RAD54L2 expression was assessed across multiple cancer types, including HNSCC, using data sourced from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). Through R-based analysis of RNA-seq data from TCGA-HNSCC, differentially expressed genes (DEGs) were identified between tumors with high and low RAD54L2 expression. RAD54L2 may be a useful diagnostic and prognostic biomarker in HNSCC. Using various statistical methods, we explored the relationship between RAD54L2 levels and immune cell infiltration, DNA methylation patterns and genetic alterations in RAD54L2, RAD54L2 expression with clinicopathological features of HNSCC patients, and the diagnostic and prognostic utility of RAD54L2. Its expression was markedly upregulated in tumor tissues versus controls. RAD54L2 expression exhibited significant correlations with immune infiltration, cell cycle genes, and androgen receptor (AR) in HNSCC. DNA methylation levels at three CpG sites within the RAD54L2 gene were linked to patient prognosis. Furthermore, RAD54L2 expression was associated with multiple clinicopathological variables, including M, N, and T stages, age, gender, race, tumor status, and overall stage. ROC analysis and nomogram model indicated that RAD54L2 effectively discriminated HNSCC from non-tumor tissues. These findings underscore the potential diagnostic and prognostic utility of RAD54L2, supporting its promise as a therapeutic target in HNSCC.